An evaluation of the accuracy of the ORange® (Gen II) by comparing it to the IOLMaster® in the prediction of postoperative refraction - Chen M (Dove Medical Press, 2012)
Ming ChenDepartment of Surgery, Division of Ophthalmology, John A Burns School of Medicine, University of Hawaii, Honolulu, HI, USAPurpose: The aim of this study was to evaluate the accuracy of ORange® Gen II (WaveTec Vision, Aliso Viejo, CA).Setting: The Surgical Suites, Honolulu, HI.Methods: The prospective 28 consecutive cataract surgical cases were selected from 85 cataract surgical cases between December 16, 2010 and February 24, 2011. With the same intraocular lens implantation, the predicted spherical equivalent refraction from IOLMaster® (Carl Zeiss AG, Oberkochen, Germany) and ORange Gen II were statistically compared and verified with 1-month postoperative manifest refraction. The data were put into IBM SPSS 19 (SPSS Inc, Chicago, IL) for analysis of variance. Pearson's correlation coefficient was also calculated to evaluate the correlation between the IOLMaster, ORange Gen II, and 1-month postoperative manifest refraction.Results: There were no statistically significant differences in the mean spherical equivalent refraction from the IOLMaster, ORange Gen II, and 1-month postoperative manifest refraction (IOLMaster -0.40 diopters, P = 0.07; ORange Gen II -0.43 diopters, P = 0.16; 1-month refraction -0.41 diopters, P = 0.07). Pearson’s correlation study demonstrated that all three were positively correlated (P < 0.05), with the strongest correlation between the ORange Gen II and 1-month postoperative manifest refraction (r = +0.6, P < 0.01).Conclusion: The ORange Gen II can be considered as an alternative method for intraocular lens selection for cataract patients.Keywords: cataract surgery, phacoemulsification, IOL implantation, IOLMaster®, ORange® Gen II, postoperative refraction